LOCAL INVOLVEMENT IN TOURISM WITH SPECIAL REFERENCE TO WOMEN AT BEKAL FORT REGION IN KASARAGOD, KERALA, INDIA - Joseph PD (EPRA International Journal of Economic and Business Review, 2014)
T he tourism sector is always deferred with a huge potential for growth, and thus become crucial not only for the nations, but also for the entire international community. The tourism proved to be one of the most effective means of job creation and the economic development of local communities. Tourism has shown that the potential for the creation of jobs and the promotion of income-generating activities in favour of the local and regional authorities. Certainly tourism offers many gateways for the employment of women and the possibilities of job creation independent of the small and medium- sized income generating activities, the creation of railway undertakings after the removal of the poverty of the women and of the municipalities in the developing countries. Tourism provides employment opportunities in a large number. Today, millions of women are a part of the tourism industry, both directly and indirectly. The tourism industry has contributed positively to the empowerment of women in India and throughout the world. The presence of women is seen in all sectors of tourism industry such as hotels, airlines, tour operator and travel services. Tourism development aims at improving the lives of people living in the local surroundings through responsible tourism. Studies show that in Kerala, the participation of women in tourism development activities is increasing and this has resulted in the overall development of the local community. This study includes a detail view of the participation of women in the tourism development of Bekal Fort area and understanding the problems faced by women in this sector. The researchers have used both primary and secondary data to evaluate the role of women in tourism in the study area. A self-structured questionnaire was distributed among 100 local women who are residing at the Bekal Fort area to draw the conclusions. It is revealed from the study that the participation of women in tourism in the study area is pretty less compared to the other sectors of the economy.